Computational analysis of database information from gene expresson repositories on cell/tissues inhuman colorectal cancer - Koik, Yen Shin. (Universiti Malaysia Sarawak (UNIMAS), 2010)
Alternation of genes expression is frequently observed in colorectal cancer (CRC). However, the precise relationship between genetic mechanism and cancer occurrence of colorectal system is poorly understood. Developmental genes are a target for the development of colorectal system and CRC establishment. Our study identifies the development genes and investigates the biological pathway and function which triggers colorectal cancer development. The genes involved in cancer development were collected from the literatures and subsequently compared with the expression information in the Cancer Gene Anatomy Project Cancer Gene (CGAP) and Cancer Gene Expression Database (CGED). A total of 227 significant developmental genes were identified. These genes were further analyzed by CateGOrizer for gene ontology term analysis. The KEGG Spider and R Spider were used for constructing the inferred gene interaction network model. The Pathway Interaction Database was used to support the result in pathway analysis. The putative gene-gene interaction network model suggested that these 10 biological processes and 5 metabolism play significant regulation roles in colorectal system. Our results suggested that apoptosis process and fatty acid metabolism have the possibility to contribute to colorectal cancer development. The vimentin (VIM), tenascin (TNC), catenin and caspases genes have biological funtioning role in embtyogenesis of colorectal system and the yact as a precursor for the apoptosis process in colorectal cancer. Abnormal expression in VIM and TNC can indirectly suppress apoptosis process. Hence, we suggest that VIM and TNC have high potential to act as colorectal disease markers.